Methodological approaches to the study of HR-brand of the company ("Journal "U". Economy. Management. Finance.", 2024)
The article analyzes the essence and structure of an HR brand, as well as methodological approaches to studying the external and internal HR brand of a company. HR branding is presented as a set of targeted activities aimed at constantly attracting the best specialists in their industry. A review of scientific and methodological literature is provided. A general description of the most popular quantitative and qualitative methods for studying various elements of an HR brand is given.
Keywords: HR-brand; employer brand management; external and internal employer brand; quantitative and qualitative methods